Risk assessment for the integrated energy system using a hesitant fuzzy multi-criteria decision-making framework - Fangqiu Xu; Kaiye Gao; Bowen Xiao; Jicheng Liu; Zixuan Wu (Energy Reports, 2022)
The carbon neutrality target challenges the reliability of integrated energy system (IES) and therefore it is necessary to assess the comprehensive risk of IES projects for investors and managers. This work proposes a hesitant fuzzy multi-criteria decision-making framework to assess the risk of IES. In this framework, 16 risk factors are firstly identified from economy, technology, politics, society and management. Then, the HF-DEMATEL-CPT approach is proposed to assess the IES risk by combining the hesitant fuzzy sets (HFS), decision-making trial and evaluation laboratory (DEMATEL) and cumulative prospect theory (CPT). Finally, a case is studied to analyze the risk factors of IES and assess the risks of four IES alternatives. The results show that there are 8 causal factors and 8 effect factors in IES risks and A3 is selected as the optimal solution. The sensitivity analysis is presented to prove the robustness of the result. Moreover, the proposed method is compared with other three risk assessment methods to show its superiority. Therefore, this study provides an effective and practical framework for IES risk assessment.